2014
DOI: 10.1111/jfir.12032
|View full text |Cite
|
Sign up to set email alerts
|

Cash Flows, Currency Risk, and the Cost of Capital

Abstract: Currency fluctuations can affect firms' cash flows. There is evidence that cash flows are related to a covariance risk factor in global stock markets. Taken together, these two lines of research suggest that the underlying link between currency movements and stock returns may be the cash flow. We test this transmission mechanism with the mimicking portfolio approach. Empirically, we find that our test assets have significant exposure to the currency factor‐mimicking portfolio and this factor carries a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…They regress changes in cash flows normalised by assets on changes in currency value and treat this coefficient as currency risk exposure. Analysing US data from 1980 to 2008, the authors tested a Carhart Four Factor Model without a high-minus-low factor, but with a currency factor, and concluded that currency risk premium is significant and usually positive [38]. Alternatively, one can try volatility of exchange rate as a base for a currency risk factor: it could be either a change in volatility or the difference in returns of currency volatility between sensitive and insensitive firms.…”
Section: Higher School Of Economicsmentioning
confidence: 99%
“…They regress changes in cash flows normalised by assets on changes in currency value and treat this coefficient as currency risk exposure. Analysing US data from 1980 to 2008, the authors tested a Carhart Four Factor Model without a high-minus-low factor, but with a currency factor, and concluded that currency risk premium is significant and usually positive [38]. Alternatively, one can try volatility of exchange rate as a base for a currency risk factor: it could be either a change in volatility or the difference in returns of currency volatility between sensitive and insensitive firms.…”
Section: Higher School Of Economicsmentioning
confidence: 99%
“…Early unconditional tests (e.g., Jorion , ) find that U.S. stocks are generally not sensitive to currency fluctuations and that there is no significant relation between currency risk and mean excess returns across U.S. stocks. More recent conditional tests (e.g., Francis, Hasan, and Hunter ) suggest that currency risk is indeed priced in the U.S. equity market and that the currency risk premium depends on U.S. macroeconomic conditions (e.g., U.S. monetary policy) (see also Bodnar and Gentry ; Bartov and Bodnar ; Chow, Lee, and Solt ; Allayannis and Ihrig ; Dominguez and Tesar ; Williamson ; Bodnar, Dumas, and Marston ; Kolari, Moorman, and Sorescu ; Bartram, Brown, and Minton ; Balvers and Klein ; Du and Hu ).…”
Section: Introductionmentioning
confidence: 99%
“… Non-accounting-factor-based models (Sercu 1980, Stulz, 1995; and  Accounting-factor-based models (Balvers and Klien, 2013, Du and Hu, 2014, Francis et al, 2008.…”
Section: Capital Asset Pricing Model (Capm) Development and Currency ...mentioning
confidence: 99%
“…Cash flow has been discussed to be one of the effective proxies for being the linking factor between the currency sensitivity and the stock performance (Hou, Karolyi and Kho, 2011). The CAPM-based model with currency risk premium of this study has been motivated by the risk premium model that uses cash flow as the proxy for the currency risk premium (Du and Hu, 2014). The portfolio approach used by Du and Hu provides the benefit of nonlinear and time-varying currency risk exposure.…”
Section: Selected Currency Risk Premium Model 21mentioning
confidence: 99%
See 1 more Smart Citation